A top-down cutting method for construction of high-performance fiber-shaped quasi-solid-state asymmetric supercapacitors. (September 2021) - Yu, N.; Li, Y.; Wang, L.; Wang, X.; Sun, Z.; Li, Z.; Luo, J.; Cao, M.; Guo, K.
Abstract: Fiber-shaped asymmetric supercapacitors (FSASCs) have great potential as a future wearable energy storage system because of good weavability, a wide operating voltage window, and high energy density. Conventional bottom-up construction methods for fiber supercapacitors are time-consuming or highly costly. This work proposes a novel facile top-down cutting method to construct FSASCs. FSASCs with desired sizes can be rapidly constructed and easily scaled up by cutting a thin-film supercapacitor into fiber-shaped devices. Serial and parallel FSASCs free of external wire connection were assembled by cutting stacked film supercapacitors and multiplying the cutting width, respectively. Besides, the as-prepared FSASCs exhibit superior comprehensive electrochemical performance, including a high volumetric capacitance of 14.7 F/cm 3, a high energy density of 93.5 μWh/cm 2, and excellent flexibility. The cutting method with advantages of high simplicity, low cost, and high efficiency may be a general construction method for fiber-shaped energy storage devices. Graphical abstract: A novel facile top-down cutting method with advantages of low cost and high agility is proposed for scalable fabrication of high-performance asymmetric fiber supercapacitors. Image 1 Highlights: A top-down strategy and alternative cutting method for constructing fiber-shaped supercapacitors were proposed. The cutting method is of low cost, facile, highly efficient, and agile. Serial and parallel fiber-shaped asymmetric supercapacitors (FSASCs) without external connection were readily obtained. The cutting method may become a general method to construct fiber-shaped energy storage devices. The as-prepared FSASC shows superior comprehensive electrochemical performance.